2020
DOI: 10.1097/j.jcrs.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Differential optical density of fluid in capsular bag distension syndrome

Abstract: Capsular bag distension syndrome (CBDS) is a rare complication of cataract surgery due to collection of fluid behind the intraocular lens (IOL). Nd:Yag laser capsulotomy is commonly performed to release the fluid collection; however, the potential risk of infection and inflammation has led to adaptation of numerous surgical procedures. Clinical examination in an established case of CBDS reveals opalescent fluid behind the IOL with ballooning of the posterior capsule, which has different reflectivity on optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Studies have shown that[ 21 , 22 ] IOL implantation may lead to capsular bag collapse and increase α-smooth muscle actin expression if the lens epithelium remains in the anterior part of the capsule, leading to anterior capsule contraction. Furthermore, fibrosis of the lens epithelium behind the capsule may further affect the visual quality, underscoring the importance of capsule management[ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that[ 21 , 22 ] IOL implantation may lead to capsular bag collapse and increase α-smooth muscle actin expression if the lens epithelium remains in the anterior part of the capsule, leading to anterior capsule contraction. Furthermore, fibrosis of the lens epithelium behind the capsule may further affect the visual quality, underscoring the importance of capsule management[ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…While evaluating an iris cyst, it is crucial to rule out iris melanoma, which appears as a brown or variably colored lesion arising from the stroma, maintaining constant contour even after pupillary dilation and possibly having sentinel or intrinsic vessels [ 6 ]. Ultrasound biomicroscopy (UBM) is usually the recommended modality for the imaging of iris cysts, which displays high reflectivity of the cyst wall; however, OCT characteristics are not well described in literature [ 7 ]. As documented in this report, the OCT findings substantiate similar findings, as noted in the UBM studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, a step ladder approach should be adapted, and treatment should be individualized based on the clinical picture. The OCT seems to be a promising tool for imaging the cyst and optical properties of the fluid on imageJ software may prove to be an objective method, useful for the diagnosis and follow-up of such patients, as it was recently reported in capsular block distension syndrome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%